Do children’s previous physical activity habits influence their behaviors during the Covid-19 social distancing period? - Siegle, Cristhina (2022)
Objective: Verify whether the practice of physical activity, before the social distancing imposed by COVID-19, influences children’s routines during this period, in children of different ages. Methods: Descriptive cross-sectional study carried out with an online questionnaire from LimeSurvey and disseminated for four months during social distancing. The questionnaire contained questions about family composition, household characteristics, household and children’s routines, including habits such as sleeping, physical activity, intellectual activity, playing with and without physical activity, and screen time. The final sample consisted of 916 participating families that answered about the physical activity habits of their respective children before the pandemic. Children were divided into three age groups (three to five years, six to nine years, and ten to twelve years). Independent Student’s t-tests were performed to investigate whether the previous practice of scheduled physical activity group and the no physical activity group differed as to the time dedicated to children’s activities and routines (intellectual activity, sleeping, screen time, playing with and without physical activity), by age groups, during social distancing. Results: There was a decrease in the levels of physical activity undertaken by Brazilian children during social distancing. There was no difference when both groups. The children with previous practice of scheduled physical activity did not display different habits from the children who did not adopt this practice. Conclusions: The practice of physical activity before social distancing did not influence the level of physical activity and other habits during social distancing. Healthy habits should be encouraged and targeted for all children during the pandemic. These findings can contribute to the formulation of public policies for children during pandemic times.